I cried to dream again : trafficking, murder, and deliverance : a memoir - Kruzan, Sara, 1978-; Thomas, Cori (Pantheon Books, 2022)
"At once disturbing and empowering, the memoir of a courageous woman, who, between the ages of thirteen and sixteen, was manipulated, exploited, and abused as a sex worker; who killed her pimp/father figure--and was unjustly sentenced to life in prison without parole. "I was 11 when I met GG. I realized later that he had to have been aware of the chaos that was my life... because he played me perfectly. I was walking home after school... I heard his red Mustang purring like a huge lion behind me before it pulled up catty corner and cut off my path. He leaned out of the open window and motioned with his right hand that I should come closer. 'Hey, excuse me.' I popped down to the window and politely, cheerfully and helpfully replied, 'Yes?' He said, 'I've been noticing you a lot, and I just want to talk to you. I'm gonna go get some ice cream and go to the park. I would love for you to come and join me. We won't be gone long. Is that okay with you?' The appeal of ice cream for me was like, 'YES! I want ice cream.' He leaned over and opened the passenger door, 'What's your name? People call me GG.' I shyly answered, 'Sara.'""--